Introducing Dyadic Interviews as a Method for Collecting Qualitative Data. (September 2013) - Morgan, David L.; Ataie, Jutta; Carder, Paula; Hoffman, Kim
In dyadic interviews, two participants interact in response to open-ended research questions. There are few precedents for using dyadic interviews as a technique for qualitative research. We introduce this method largely in comparison to focus groups, because both represent forms of interactive interviewing. We do not, however, view dyadic interviews as miniature focus groups, and treat them as generating their own opportunities and issues. To illustrate the nature of dyadic interviewing, we present summaries of three studies using this method. In the first study, we used dyadic interviews and photovoice techniques to examine experiences of people with early-stage dementia. In the second study, we explored the experiences of staff who provided services to elderly housing residents. In the third study, we examined barriers and facilitators to substance abuse treatment among Asian Americans and Pacific Islanders in Hawaii. We conclude with a discussion of directions for future research using dyadic interviews.